An evaluation of safety and survival for patients with locally advanced pancreatic cancer treated with irreversible electroporation combined with chemotherapy: a retrospectively observational study. Issue 1 (15th March 2022) - He, Chaobin; Wang, Jun; Mao, Yize; Lao, Xiangming; Li, Shengping
Abstract: Objective: Irreversible electroporation (IRE) is emerging as a new therapy for locally advanced pancreatic cancer (LAPC). We aimed to conduct survival and safety analyses in LAPC patients after treatment with IRE combined with chemotherapy. Methods: A total of 64 patients with LAPC who had received IRE and chemotherapy were retrospectively collected from August 2015 to March 2019 at Sun Yat-sen University Cancer Center. Overall survival (OS) and progression-free survival (PFS) were evaluated using Kaplan-Meier method and compared by the log-rank test. A multivariate Cox regression model was used to determine the prognostic factors of survival. The perioperative complications of IRE were also evaluated. The study was approved by the Institutional Review Board of Sun Yat-sen University Cancer Center (approval No. C2021-003). Results: The median survival of all included patients were 24.63 (95% confidence interval: 21.78–27.49) for overall survival and 13.00 (95% confidence interval: 8.81–17.19) months for progression-free survival, with 96.8%, 51.9%, 18.3%; and 52.3%, 21.5%, 7.9% as the 1-, 2- and 3-year OS and PFS rates, respectively. Tumor size [OS, hazard ratio (HR)=1.768, P = 0.048; PFS, HR = 0.304, P = 0.010], neoadjuvant chemotherapy (OS, HR = 0.338, P = 0.030; PFS, HR = 0.358, P = 0.034), carbohydrate antigen 19-9 variation after IRE (OS, HR = 19.320, P = 0.003; PFS, HR = 14.591, P = 0.021) and tumor response after neoadjuvant chemotherapy (OS, HR = 8.779, P = 0.033; PFS, HR = 5.562, P = 0.008) were predictive factors of survival in patients with LAPC after IRE. Complications were observed in 20.3% of patients. Grade B pancreatic fistula was the most common complication. The complication rates of the late treatment group (6.1%) were significantly lower than those of the first 15 patients after IRE treatment (66.7%). The median length of hospital stay of late treatment group was 8.6 days, which was also shorter than that of the early treatment group (10.0 days). Conclusions: IRE combined with chemotherapy could improve survival of LAPC patients with acceptable complication rates. Therefore, it may be a suitable method for LAPC but should be validated in prospective randomized trials.